Plan de marketing operativo en la dulcería tradicional los Almendros agencia Rocafuerte - Figueroa Delgado, Jairo Francisco (2020)
The purpose of this research was to propose an operational marketing plan that contributes to increase the sales and positioning in new areas of the traditional Los Almendros candy store in the city of Rocafuerte. For data collection and subsequent analysis, use different techniques including: interview, survey, competitive profile matrix, SWOT analysis and Porter's 5 forces analysis, being very useful in determining the plan marketing that best suits the needs of the candy store. The results shown not only the internal factors of the candy store situation, among which stand out: good geographical location, satisfactory attention, quality in products and services, little business advertising, etc.; but also the external factors like the economic, social, political situation, among others. The analysis allowed identifying the main competitors of the candy store and making a comparison. With all this feedback, the information was obtained that served as the basis for proposing the respective operational objectives, strategies, corresponding action plan and strategic direction necessary for implementation. Subsequently, the operational objectives, the strategies and the corresponding action plan will also be raised, including advertising campaigns in the media and social networks, finally the action plan will be concluded, it is the guide to prioritize the most important activities to meet the objectives and goals.